(untitled) (Medico Legal Update, 2020)
Background: Birth asphyxia is neonates’ inability to activate and sustain breathing at conception .. It is also recognized as a condition that arises when blood gas delivery is compromised, contributing to hypoxemia and hypercapnia The combination of hypoxia and ischemia may contribute to a cascade of biochemical changes in the body contributing to neuronal brain loss and brain harm Objectives: In order the aim of study to Identify the demographic characteristic of sample , Identify knowledge of nurses in caring of neonate with birth asphyxia at NICU at pediatric hospitals in Babylon governorate , determine the relationship between nurses knowledge with birth asphyxia at NICU with certain of socio- demographic characteristics of sample Babylon, Iraq. Methodology: A comprehensive research is undertaken to investigate nurses’ understanding of Neonate with Birth Asphyxia in the Neonatal Intensive Care Unit at Babylon Governorate Pediatric Hospitals A randomized random sample of (62) nurse is chosen with the usage of the chance sampling method. The research group is spread in the Neonatal Intensive Care Unit at Babylon Governorate Pediatric Hospitals. The data was obtained using a built-in self-report questionnaire and evaluated using the concise statistical analysis method that involves “frequencies & percentages” and the Inferential statistical data analysis methodology used for the Chi-square test. Results: Results of the analysis show that the participants with excellent awareness served (66.1 percent), whereas those with bad information (33.9 percent) reflected nurses in the Neonatal Intensive Care Unit at the Babylon Governorate Pediatric Hospitals. In comparison, the mean age of experienced nurses is 32.73 ± 9.33 while those with bad awareness are 26.05 ± 5.86. Significant linkages exist between Education and awareness engagement, p = 0.015. Conclusions and recommendations : Around 66 per cent of nurses have experience of birth asphyxia, the study showed. Despite Born Asphyxia, about half of them have strong and optimistic disposition towards Neonate. Education will be deemed to improve nurses’ awareness of Neonate with Birth Asphyxia